2013
DOI: 10.5535/arm.2013.37.4.534
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Anxiety and Pain After Whole Body Whirlpool Hydrotherapy Among Patients With Myofascial Pain Syndrome

Abstract: ObjectiveTo evaluate the effect of the Whirlpool hydrotherapy on pain and anxiety in chronic myofascial pain syndrome (MPS) patients, compared to the conventional hydrocollator pack therapy.MethodsForty-one subjects who have MPS in the upper trapezius muscles without depression were recruited. The patients were randomly assigned into two groups: the whirlpool therapy group whose bodies were immersed in a whirlpool bath at 34℃-36℃ for 30 minutes; the hydrocollator group who took a 30-minute application of a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…And counter to our expectations, the study patients with mild to moderate OA did not express a depressive mood, anxiety, or low QoL at baseline. This result was contrary to our previous study in chronic myofascial pain syndrome 36) . That might be due to the pain severity.…”
Section: Discussioncontrasting
confidence: 99%
“…And counter to our expectations, the study patients with mild to moderate OA did not express a depressive mood, anxiety, or low QoL at baseline. This result was contrary to our previous study in chronic myofascial pain syndrome 36) . That might be due to the pain severity.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study with 41 subjects who have myofascial pain syndrome, the patients were randomly assigned into two groups: the whirlpool therapy group whose bodies were immersed in a whirlpool bath at 34°C-36°C for 30 minutes; the hydrocollator group who took a 30-minute application of a standard hot hydrocollator pack [32]. At the end of the study the improvement on pain and anxiety was significantly greater in the whirlpool group, compared to the hydrocollator group [32]. This result was explained by the gate theory; Due to the pressure and thermal temperature of hydrotherapy on the skin pain is relieved [33].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature on the effectiveness of balneotherapy reported that balneotherapy improved depression and anxiety (Clark-Kennedy et al, 2021). In the study by Im and Han, whirlpool hydrotherapy was found to reduce anxiety significantly more than hot compresses (Im & Han, 2013). In a systematic review of the effectiveness of hydrotherapy during labor, it was found that hydrotherapy reduced maternal anxiety (Shaw-Battista, 2017).…”
Section: Subgroup Analysismentioning
confidence: 99%